Лазерный нагрев и структура стали атлас микроструктур - Садовский В. Д. Виссарион Дмитриевич; Счастливцев В. М. Вадим Михайлович; Табатчикова Т. И. Татьяна Инокентьевна; Яковлева И. Л. Ирина Леонидовна; Сагарадзе В. В. (Свердловск, УрО АН СССР, 1989)
Исключено из фонда НТБ ТПУ